Modeling of giant magnetostrictive vibration energy harvesting. Issue 2 (March 2019) - Bai, Guo; He, Zhongbo; Zhou, Jingtao; Rong, Ce; Zheng, Jiawei
Abstract: Vibration energy recovery technology, as an important way to alleviate energy pressure, has a broad application prospect in the electromechanical field. With the excellent performance of giant magnetostrictive materials (GMM), the giant magnetostrictive vibration energy recovery technology has attracted attention. In view of the shortcomings of current giant magnetostrictive vibration energy recovery research, this paper designs a column-rod vibration energy recovery device based on the material properties of giant magnetostrictive materials, and introduces its working principles. Combined with the structural characteristics of the device, this paper establishes the output model of the energy recovery process, calculates and analyzes the voltage output of the energy recovery, and obtains the output curves under different excitation energies were obtained, providing reference for the optimal design of the device and its further engineering application.